The Lived-Experiences of African Migrant Professionals in Diverse Workplaces in Australia - Bolaji, Stephen; Imonitie, Olabisi (Journal of Ethnic and Cultural Studies, 2025)
This study examines the lived experiences of 44 African migrant professionals in Australian workplaces. Using phenomenological inquiry and thematic analysis, the research explored the challenges these professionals face and the coping mechanisms they employ in navigating workplace dynamics across various industries. This paper highlights three significant challenges identified in the findings: the pervasive nature of microaggressions and subtle biases in professional interactions, unspoken challenges and the emergence of inter-migrant discrimination, a phenomenon previously underexplored in Australian workplace studies. The research also revealed various coping strategies employed by these professionals, including striving for performance excellence, affirming cultural pride and identity, and cultivating a positive mindset. This research contributes to the literature on workplace diversity by revealing the nuanced interplay between cultural identity, professional recognition, and workplace inclusion. The findings offer practical insights for organisations seeking to move beyond superficial diversity initiatives towards creating genuinely inclusive environments that value diverse perspectives and experiences in the Australian professional context.